AB0147 Oxidative stress and flogosis: The role of endothelial progenitor cells in rheumathoid arthtritis. (23rd January 2014) - Lo Gullo, A.; Mandraffino, G.; Sardo, A.; D'Ascola, A.; Imbalzano, E.; Saitta, C.; Cinquegrani, M.; Lo Gullo, R.; Bagnato, G.; Bagnato, G.; Saitta, A.
Abstract : Background: Patients affected by Rheumathoid arthtritis (RA) present accelerated atherosclerosis and increased cardiovascular morbidity and mortality, with respect to the general population. In RA an impairment of the number and the activity of circulating progenitor cells, including CD34+ cells and endothelial progenitor cells (EPC), is involved in development of endothelial damage and cardiovascular diseases (CVD). Objectives: This study explores the effects of oxidative stress and flogosis on endothelial progenitor cell property and activity. Methods: Circulating progenitor cells (CPCs) were isolated from 33 pz affected by RA and from 33 controls matched for age and gender. In these cells mRNA expression, protein levels and enzymatic activity of antioxidants: manganese superoxide dismutase (MnSOD), catalase (CAT), and glutathione peroxidase-type 1 (GPx-1) were evaluated. C-reactive protein (CRP) levels were measured. We also investigated the accumulation of intracellular reactive oxygen species (ROS) in CPCs and the relationships among some inflammatory markers and cell number and enzymes. Results: In RA CPCs number (0.39±0.10 vs 0.62±0.08, p<0.001) was significantly reduced. Intracellular ROS levels (107.35±73.36 vs 49.19±10.70, p<0.001) were higher, as well as MnSOD (mRNA, protein and activity), while CAT and GPx-1 (mRNA, proteins and activity) were reduced. CPCs number was correlated with CRP, ROS and enzyme levels and activity. In patients with RA the levels of CRP correlates linearly with the expression of MnSOD (rs=0.63, p<0.001), with levels of ROS (rs=0.51, p<0.001), with biomarkers of arterial stiffness (PWV, rs=0.44, p<0.005; AI%, rs=0.36, p<0.01) while appears not correlate with CAT or GPx-1 (rs=0.08, and rs=0.04, respectively, both p=ns). CPCs number correlate inversely with arterial stiffness indices (PWV, rs 0.48 p<0.001, AI, rs 0.73, p<0.001). Conclusions: Our data show that in RA inflammation and oxidative stress impair CPCs antioxidant system, reduce their number in peripheral blood, induce the develop of endothelial damage leading to accelerated atherosclerosis. References: Silverman MD et al. The role of vascular cell adhesion molecule 1/very late activation antigen 4 in endothelial progenitor cell recruitment to rheumatoid arthritis synovium. Arthritis Rheum 2007;56(6):1817-26. Herbrig K et al. Endothelial dysfunction in patients with rheumatoid arthritis is associated with a reduced number and impaired function of endothelial progenitor cells. Ann Rheum Dis 2006;65(2):157-63. He T et al. Human endothelial progenitor cells tolerate oxidative stress due to intrinsically high expression of manganese superoxide dismutase. Arterioscler Thromb Vasc Biol 2004;24(11):2021-7. Tousoulis D et al. Role of inflammation and oxidative stress in endothelial progenitor cell function and mobilization: therapeutic implications for cardiovascular diseases. Atherosclerosis 2008;201(2):236-47. Verma S et al. C-reactive protein attenuates endothelial progenitor cell survival, differentiation, and function: further evidence of a mechanistic link between C-reactive protein and cardiovascular disease. Circulation 2004;109(17):2058-67. Disclosure of Interest: None Declared